(untitled) (The Journal of Psychology and Sociology, 2019)
The 21st century is a time of complex social changes and historical events, the influence of globalization in society is deep, the time of the formation of global consciousness. Profound socio-economic and historical changes affect the volume and nature of migration processes. Migration of the population as a social process and social change requires a deep and comprehensive study in domestic science. The article analyzes sociological theories in the field of population migration, they are grouped and classified according to the directions of explanation of the migration process. The purpose of the article is a review of scientific papers explaining the phenomenon of migration and the grouping of world migration theory from the standpoint of the main sociological paradigms. The synthesis of world migration theories from the point of view of the main sociological schools allows for a deeper description, understanding and study of the phenomenon of population migration. The article also provides a comparative critical analysis of the impact of global migration trends on the migration status in modern Kazakhstan. In the course of writing this article, the authors used the methodology for classifying the world’s leading theories in the field of migration into the main scientific paradigms in sociology. In modern sociological science there are several scientific complementary paradigms explaining social processes and phenomena at the macro and micro levels. A detailed description of this approach is presented in the three main paradigms: the first structural and functional direction, which puts social systems at the head of the study. The structural-functional paradigm considers migration as a social phenomenon and social process at the macro level and explains the causes of migration with the level of development of structural systems in society, especially economic ones. Theories explaining the causes of migration at the micro level are mainly owned by sociologists. A distinctive characteristic of such a theory is an understanding of the characteristics of individual and interpersonal relations in a certain situation, those that are in the foreground are people and their behavior, as well as their social interactions in everyday life. The third group of the theory, explaining the reasons for migration, belongs to integrative paradigms in sociological science, they explain the migration process at two levels: structural and personal. Integrative paradigms analyze social reality simultaneously with objective and subjective, structural and dynamic, social and individual points of view. These theories are new theories in the field of migration, which consider the need to study the effects on migration and the level of development of structural systems, and individual and individual factors. Analyzing advanced theories explaining migration, the authors propose to classify migration theories based on a four-dimensional model of understanding the social structure of P. Shtompka. Keywords: Migration, Factors of Rural-Urban Migration, Structural-Functional Analysis, Social changes, The Impact of Globalization on Migration.